Covalent organic frameworks with immobilized anions to liberate lithium ions: Quasi-solid electrolytes with enhanced rate capabilities. (1st September 2021) - Tian, Xiaolu; Chen, Shuhui; Zhang, Peng; Yang, Pu; Yi, Yikun; Wang, Te; Fang, Binren; Liu, Pei; Qu, Long; Li, Mingtao; Ma, Heping
Highlights: Covalent organic frameworks loading ionic liquid show high ionic conductivity. Covalent organic frameworks and ionic liquid exhibit strong interactions. Lithium-ions transference number is increased. Improved rate capability at 0.5 and 1C is achieved. Abstract: Ionic liquids (ILs) are promising candidates as fast Li + conductors owing to their high ionic conductivity and admirable stability. However, the mobile ions in ILs will contribute to the overall ion conductivity which decreases Li ions transfer efficiency and rate capability of batteries. The improvemnt of Li ions transfer efficiency in ILs electrolyte materials is a great challenge. Covalent organic frameworks (COFs) with high porosity and aligned nanosize channels can offer free flowing pathways for Li + migration as well as abundant active sites to anchor anions and liberate free Li +, which can maximize Li + transfer efficiency. Herein we design a cationic COF and a neutral COF as porous hosts for immobilizing the anions of IL N, N-diethyl-N-(2-methoxyethyl)-N-methylammoniumbis(trifluoromethylsulphonyl)imide (DEME-TFSI) to enhance Li + transference efficiency. The obtained quasi-solid COFs-IL electrolytes exhibit high IL loading amount owing to strong interactions between COFs and the IL. Moreover, COFs-IL electrolytes show good electrochemical stability and high ionic conductivity over 1×10 −3 S cm −1, along with a 90% increase of Li + transfer number in comparison to the bare IL electrolyte (IL/LiTFSI). Our research provides a general strategy for immobilizing mobile anions to liberate Li + and improve Li + transfer efficiency in IL-based electrolytes. Graphical abstract: Image, graphical abstract